Investigation of Learning Loss in the Aspect of Cognitive and Attitude Competence of Students in the Islamic Education Subject in SD Muhammadiyah - Nurchamidah; Mirza Mahbub Wijaya; Nur Laela; Rafi Pradipa; Baso Syafaruddin; Muhammad Hamsah (al-Afkar, Journal For Islamic Studies, 2025)
The current transformation of the education system from face-to-face learning to online learning has caused many problems in terms of student learning motivation, learning models, and learning climate. This research aims to explore the facts that occur related to learning loss in the cognitive and affective domains. This research uses the case study method to explore a case related to learning loss in students at SD Muhammadiyah Jogokarian. Data collection techniques were carried out by means of interviews, observations, and documentation to school residents. The data in this study were analyzed using the triangulation method. The results of this study show that students' learning loss in cognitive aspects such as weak motivation to learn, low learning evaluation results, and low levels of student understanding of PAI material, even 20% have decreased learning outcomes. Meanwhile, in the attitude aspect, there is a decrease in the ability of discipline, social care, environmental care, and low curiosity because they have not fully understood the online learning pattern. PAI teachers also experienced obstacles where PAI teachers were unable to understand optimally due to the limited video media sent by students online, the difficulties experienced by PAI students in the practice of PAI materials in the form of ablution recitation, prayer recitation, and letter memorization.